Bahasa Dan Kekuasaan Dalam Wacana Politik: Analisis Wacana Historis Ruth Wodak Terhadap Pidato Presiden Joko Widodo - Aprilya Siahaan; Ayu Aldina Afriyanti; Elia Milane Nainggolan; Evi Rizkita Dewi; Lasenna Siallagan; Rianti Rianti; Yoyuti Sonata Capah (FKIP, Universitas Palangka Raya, 2023)
This study aims to analyse the historical value in President Joko Widodo's speech in commemoration of the 75th Anniversary of the Proclamation of Independence of the Republic of Indonesia. This study used qualitative descriptive method. This research used Ruth Wodak's historical discourse analysis model. Based on the analysis result, it was found that President Joko Widodo's speech in commemoration of the 75th Anniversary of the Proclamation of Independence of the Republic of Indonesia stated 10 statements contained historical value which can influence the readers.